Hacia la Alfabetización Informacional en América Central - Miranda Arguedas, Alice (2007)
WORLD LIBRARY AND INFORMATION CONGRESS: 73RD IFLA GENERAL CONFERENCE AND COUNCIL 19-23 August 2007, Durban, South Africa http://www.ifla.org/IV/ifla73/index.htm